ELECTRONIFICATION OF INSOLVENCY PROCEEDINGS IN THE LIGHT OF THE PROTECTION OF CREDITORS' FUNDAMENTAL RIGHTS (EU and comparative law issues and challenges series (ECLIC), 2024)
The aim of our paper is to focus on the electronicisation of insolvency proceedings through the newly introduced insolvency register, which is supposed to represent a single centralised system for insolvency and liquidation proceedings with an emphasis on the protection of creditors' personal data. The European Union is also currently commenting on several issues in the area of business entities and the transparency of business activities. In the individual sections, we have focused on the approach to the computerisation of insolvency proceedings, the definition of personal data provided in insolvency proceedings by the creditors themselves, the principles of personal data protection, also outlining the case law of the Court of Justice of the European Union dealing with this area. We have also focused on the problems that have arisen in application practice in relation to the disclosure of personal data of individuals. We conclude that the legislator should focus more specifically on the protection of creditors' personal data and tighten up the possibilities of accessing it, but also consider whether its public availability is necessary.